DAMPAK PROGRAM BANTUAN SOSIAL TERHADAP PERTUMBUHAN EKONOMI DAN KEMISKINAN KABUPATEN TERTINGGAL DI INDONESIA - Edo Pramana Putra; Yeti Lis Purnamadewi; S Sahara (TATALOKA, 2015)
The issue of underdeveloped areas and the problems of inequality ofdevelopment is the disparity problem areas that endanger national unity. The purpose of this study is to examine the dynamics of poverty and the dynamics of social aid in underdeveloped areas, to analyze the effect of social aid Ministry of underdeveloped areas to economic growth in underdeveloped areas, and to analyze the relationship between economic growth and poverty reduction in underdeveloped area in Indonesia. The results showed the increase dynamics and decline of poor people in underdeveloped areas in Indonesia within the period 2010-2013. From the results of regression analysis of panel data model of economic growth known that variable social and cultural institutional support, infrastructure support, and help the world economy and a significant effort to increase economic growth in under dev eloped areas, while the human resources aid and specific support area is not significant in improving economic growth in underdeveloped regions. The results of the regression analysis poverty panel data model known that the variable number of unemployed, IPM, and the share of the services sector significantly affect to the level of poverty in underdeveloped areas, while the variable PDRB, the share of agriculture and industry sector share is not significant in influencing to the poverty level in underdeveloped area.